Physical Activity and Awareness of its Benefits Among Pregnant Women - Urbelionytė, Augustė; Zakarienė, Rasa; Liutikienė, Rasa (Slauga. Mokslas ir praktika, 2022)
Physical activity during pregnancy is crucial not only for a woman's physical health but also for her emotional health and the outcome of pregnancy and childbirth. Providing sufficient and timely information to women about the importance of physical activity during pregnancy would encourage them to exercise.Aim of the study – to analyse pregnant women's awareness of the benefits of physical activity during pregnancy.Methods. Quantitative study, online questionnaire survey conducted in March 2022. The study involved 164 pregnant women with a mean age of 30.43±4.52 years. Statistical software package SPSS 21.0 for Windows was used for data analysis.Results. 79% of the participants were pregnant for the first time and 83% of the women were 33-40 weeks pregnant at the time of the survey. The results showed a significant decrease in women's physical activity during pregnancy compared to the pre-pregnancy period, with 68.9% being physically active before pregnancy and 47.0% during pregnancy. In terms of changes in physical activity, it was found that, of those who were physically active before pregnancy, more than a quarter of the women had stopped physical activity during pregnancy. When analysing the body parts affected by pain and comparing the assessment of complaints during pregnancy according to physical activity during pregnancy, it was found that posterior pelvic pain and fatigue were statistically significantly more common in the physically inactive participants than in the physically active ones. Physically active women ranked walking, exercise, swimming, yoga as the most frequent physical activities during pregnancy and rated their health higher than physically inactive women. The study found that sources of information on the benefits of physical activity during pregnancy include: the internet, scientific articles, antenatal education and medical advice.Conclusions. Women's awareness of the benefits of physical activity during pregnancy is low.
Keywords: pregnancy; physical activity; awareness; physical and mental condition